Student Lifestyle and Social Pressure in Educational Environment - Muhibatul Muyasyaroh; Adinda Sabrina Salsabila; Muhammad Syafiurrahman; Muhammad Ryja Baihaqi; Abdul Fadhil (Konsultan Jurnal Ilmiah Indonesia, 2026)
The world of education today is not only a space for academic development but also a social arena where students' identity and existence are shaped. Along with the massive development of digital technology and social media, there has been a significant shift in student lifestyles that triggers the emergence of a consumerist culture, the